4(1-sen^2).(sec^2-1)=3
Soluções para a tarefa
Respondido por
0
Lembre-se que:
![\boxed{1-sen^2x=cos^2x}\\
\\
\boxed{sec^2x=\frac{1}{cos^2x}} \boxed{1-sen^2x=cos^2x}\\
\\
\boxed{sec^2x=\frac{1}{cos^2x}}](https://tex.z-dn.net/?f=%5Cboxed%7B1-sen%5E2x%3Dcos%5E2x%7D%5C%5C%0A%5C%5C%0A%5Cboxed%7Bsec%5E2x%3D%5Cfrac%7B1%7D%7Bcos%5E2x%7D%7D)
![4cos^2x*(\frac{1}{cos^2x}-1)=3\\
\\
cos^2x*(\frac{1}{cos^2x}-1)=\frac{3}{4}\\
\\
1-cos^2x=\frac{3}{4}\\
\\
sen^2x=\frac{3}{4}\\
\\
senx=\frac{\sqrt3}{2} \Rightarrow x=\frac{\pi}{3} \ rad =60^o 4cos^2x*(\frac{1}{cos^2x}-1)=3\\
\\
cos^2x*(\frac{1}{cos^2x}-1)=\frac{3}{4}\\
\\
1-cos^2x=\frac{3}{4}\\
\\
sen^2x=\frac{3}{4}\\
\\
senx=\frac{\sqrt3}{2} \Rightarrow x=\frac{\pi}{3} \ rad =60^o](https://tex.z-dn.net/?f=4cos%5E2x%2A%28%5Cfrac%7B1%7D%7Bcos%5E2x%7D-1%29%3D3%5C%5C%0A%5C%5C%0Acos%5E2x%2A%28%5Cfrac%7B1%7D%7Bcos%5E2x%7D-1%29%3D%5Cfrac%7B3%7D%7B4%7D%5C%5C%0A%5C%5C%0A1-cos%5E2x%3D%5Cfrac%7B3%7D%7B4%7D%5C%5C%0A%5C%5C%0Asen%5E2x%3D%5Cfrac%7B3%7D%7B4%7D%5C%5C%0A%5C%5C%0Asenx%3D%5Cfrac%7B%5Csqrt3%7D%7B2%7D+%5CRightarrow+x%3D%5Cfrac%7B%5Cpi%7D%7B3%7D+%5C+rad+%3D60%5Eo)
Perguntas interessantes
Geografia,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás